Chiral Recognition of Amino Acids by Magnetoelectrodeposited Cu Film Electrodes - Iwao Mogi; Kazuo Watanabe (International Journal of Electrochemistry)
Chiral behavior of magnetoelectrodeposited (MED) Cu film electrodes was investigated for the electrochemical reactions of amino acids. The Cu films were electrodeposited under a magnetic field of 5 T perpendicular to the electrode surface. Such MED Cu films were employed as an electrode, and cyclic voltammograms were measured for the electrochemical reactions of several kinds of amino acids. Chiral behavior was clearly observed as oxidation current difference between the enantiomers of alanine, aspartic acid, and glutamic acid. The MED film electrodes with the thickness of 50~500 nm exhibited such chiral behavior, and their surface morphologies had network structures, which could be induced by the micro-MHD effect.